Other "lights" regarding the early political history of Colombia, 1780–1850: Gaetano Filangieri and "The route from Naples to the West Indies" (2006)
Based on archival evidence, this text opens the horizon of interpretations of the ideological-political presence of the so-called European Enlightenment in America. Thus, we speak of illustrated languages and consider other illustrations that permeated mo